How do you cross multiply

4c + 12 = 3d + 9

Relevance
• 4c + 12 = 3d + 9

This being an equation,

no cross multiplication is involved.

Factorizing gives us

4(c + 12) = 3(d + 3)

• Login to reply the answers
•  You can factorize it into: 4(c+3) = 3(d+3)

• Login to reply the answers
• Anonymous
1 month ago

The equation has already been cross-multiplied...

4c + 12 = 3d + 9 ==> 4(c + 3) = 3(d + 3).

The original equation (before cross-multiplication) would be: (c + 3)/3 = (d + 3)/4.

• Login to reply the answers
• Anonymous
1 month ago

Simplify the equation: 4(c +3) = 3(d+3)

Now try.

• Login to reply the answers
• Are you trying to rewrite one variable in terms of the other?

4c = 3d + 9 - 12

4c = 3d - 3

c = 3d - 3/4

OR

4c + 12 - 9 = 3d

4c + 3 = 3d

4c/3 + 3/3 = d

4c/3 + 1 = d

• Login to reply the answers
• I never cross multiply, it's too confusing! But you can simplify.

4(c +3) = 3(d+3)

• Login to reply the answers
• (4c + 12)/1 = (3d + 9)/1

(4c + 12) × 1 = (3d + 9) × 1

• Login to reply the answers
• You can’t. You need fractions to cross multiply.

• Login to reply the answers
• Anonymous
1 month ago

What are you trying to do?

• Login to reply the answers